Introduction of amino groups into lignin and lignin model compounds: recent advances - Badazhkova, Veronika D.; Savela, Risto; Leino, Reko (Royal Society of Chemistry (RSC), 2026)
Research on lignin valorization has attracted considerable attention in recent decades. Lignin, a natural aromatic polymer, is a renewable and readily available source for producing new biobased chemicals and materials. For successful lignin valorization towards value-added products, development of efficient procedures allowing the introduction of new functionalities to its structure becomes essential. One of the approaches for chemical modification of lignin involves the introduction of amino groups. Lignin amination methodologies potentially provide aromatic amines that could be used as building blocks for the synthesis of different compounds, including pharmaceuticals and precursors for bio-based polymeric materials. Due to the complex structure of lignin, however, model compounds are commonly used for studying the reactivity and for developing lignin modification procedures. In several studies, it has been demonstrated that lignin model compounds imitating the most abundant lignin β-O-4 linkage can be converted to nitrogen containing aromatic compounds with various potential applications. However, it has also been observed in several cases that the developed amination procedures only have functioned on the model compounds but not on extracted lignin polymer. Overall, in recent years, several procedures have been developed for amination of lignin model compounds and lignin, allowing materials containing primary, secondary and tertiary amines to be obtained, for example the Mannich reaction, silylation and epoxy functionalization. The chemical modification and analysis of lignin are nevertheless hampered by its complex and inconsistent structure, varying significantly depending on the source and method of isolation. While the bulk of currently available lignin is present mainly in the form of Kraft lignin with condensed structure and low solubility, new efficient methods could facilitate switching to lignin-first approaches, preserving its original structure and improving the processing towards value-added products.